Penerapan Inovasi Media Pembelajaran PAI berbasis Heyzine Flipbook - Jannah, Miftakhul; Sanusi, Sanusi (Al-DYAS, 2025)
This study is motivated by the limited research on the use of interactive digital media in Islamic Religious Education (PAI) that explicitly integrates character values, particularly tolerance. The objective of this study is to analyze the innovation and implementation of PAI instructional media based on Heyzine Flipbook in class 8A of SMP 1 Kudus. This field research employed data collection techniques including observation, interviews, and documentation, analyzed through triangulation of sources, techniques, and time. The findings reveal that digital media developed using Canva and Heyzine Flipbook can create engaging and accessible learning experiences aligned with the characteristics of Generation Z students. This media promotes active participation, enhances learning motivation, and strengthens students’ understanding of tolerance within the context of PAI instruction. The results indicate that the integration of character values into interactive digital media holds significant potential for fostering inclusive religious attitudes. However, limitations such as students’ unfamiliarity with digital media and the narrow scope of the sample highlight areas for future development. This study contributes meaningfully to the advancement of technology-based PAI learning media while promoting the reinforcement of character values in secondary education.